Augmented superpixel based anomaly detection in hyperspectral imagery - Gökdemir, Ezgi (Graduate School, 2024)
The detection of anomalies in hyperspectral images depends on several factors. Here, the spatial proximity of anomalies and confusion in the background image can create a bottleneck at the point of anomaly detection. Hyperspectral images are tensor data, in which each pixel contains both spatial and spectral information. These complex data structures pose significant challenges for traditional anomaly detection methods, which often struggle to account for the intricate relationships between the different spectral bands. In this thesis, a method called "Augmented Superpixel (Hyperpixel) Based Anomaly Detection in Hyperspectral Imagery" is proposed. This method aims to enhance the anomaly detection by leveraging advanced dimensionality reduction and segmentation techniques. Our approach begins by reducing the three-dimensional HSI data using methods such as high-dimensional model representation and Principal Component Analysis. This step simplifies the data while preserving critical spectral and spatial information. By capturing the most significant components of the data, these techniques help eliminate noise and irrelevant details, thereby making the subsequent analysis more focused and effective. We then applied segmentation methods such as Simple Linear Iterative Clustering and Linear Spectral Clustering to divide the image into distinct regions known as superpixels. Each superpixel is augmented with its first-order neighbors to form hyperpixels, which provide a richer context for anomaly detection. The augmentation process ensures that the local context is considered, thereby enhancing the ability to detect subtle anomalies that may be missed when examining individual superpixels in isolation. This neighborhood information is crucial for accurately identifying the boundaries of anomalies and distinguishing them from normal variations in the data. Finally, we applied the Local Outlier Factor algorithm to these hyperpixels to identify the outlier points that signify anomalies. The capability of the Local Outlier Factor to evaluate local density deviations enables it to accurately identify anomalies, even in densely populated or intricate backgrounds. The combination of these techniques ensures comprehensive and precise analysis that can handle the diverse characteristics of hyperspectral datasets. The proposed algorithm was tested using various hyperspectral image datasets and demonstrated good performance in detecting anomalies. By integrating dimensionality reduction, segmentation, and anomaly detection techniques, this method effectively manages the complexity of the hyperspectral data. This comprehensive approach allows for accurate identification of anomalies, even in challenging conditions where anomalies are closely packed or the background is complex. Through rigorous experimentation, the algorithm demonstrated robustness and reliability, making it a promising tool for hyperspectral image analyses. Its versatility and high accuracy across different datasets underline its potential for broad application in fields such as remote sensing, environmental monitoring, and urban planning. The ability to adapt to various anomaly characteristics and dataset structures makes this method a valuable addition to the toolkit for hyperspectral image-analysis techniques.
Hiperspektral görüntülerde genişletilmiş süperpiksel tabanlı anomali tespiti
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: imaging; görüntüleme; hyperspectral imagery; hiperspektral görüntüleme; Informatic engineering; Bilişim mühendisliği